THE EFFECT OF CAPITAL EXPENDITURE ON REGIONAL FINANCIAL PERFORMANCE WITH REGIONAL ORIGINAL INCOME AS A MEDIATION VARIABLE - Farah Agustina Insani; R Budi Hendaris (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
In implementing their regional autonomy, regional governments provide great opportunities to improve regional financial performance, especially to be more fiscally independent. This independence means that regions should have a low level of regional dependency. However, the phenomenon that occurs is that many regional governments still have a very high regional dependency ratio. This study aims to empirically analyze how capital expenditure affects regional financial performance as measured by the regional dependency ratio with Regional Original Income as a mediating variable. The method used is the quantitative method. The data used in this study are the Budget Realization Reports of Regency/City Governments in West Java Province for 2018-2022 using purposive sampling. The study results show that capital expenditure has a negative and significant effect on regional financial performance as measured by the regional dependency ratio directly and indirectly through the mediating Regional Original Income. Regional governments must optimize capital expenditure that can increase Regional Original Income significantly to improve regional financial performance by reducing the regional dependency ratio.